THE RISE OF AXIOLOGICAL ATTITUDE TO THE GENRE OF SHASHMAQAM, WHICH IS INCLUDED IN THE CONTENT OF INTANGIBLE CULTURAL HERITAGE - Kirgizov Iqboljon Imyaminovich (Journal of Learning on History and Social Sciences, 2024)
In the article, globalization processes have created the need for an axiological approach to intangible cultural heritage in the world community. That is why it is important to convey intangible cultural heritage as a value to the next generation in its pure state. In these processes, every nation with an ancient and rich history and the representatives of this nation polish over the centuries and preserve the examples of folk art and folk art, and today Uzbekistan has included local objects in the UNESCO World Heritage List. as a priority to include items, the state decisions defined in the "Strategy of Actions" and "Strategy of Development" are also of great importance, and the concept of "Intangible Cultural Heritage" includes our cultural heritage that has reached the present day from our ancestors